Comparable efficacy and safety of brodalumab in obese and nonobese patients with psoriasis: analysis of two randomized controlled trials. (16th October 2019) - Hsu, S.; Green, L.J.; Lebwohl, M.G.; Wu, J.J.; Blauvelt, A.; Jacobson, A.A.
Summary: Background: Obesity is associated with psoriasis and negatively affects response to therapy. Objectives: To evaluate the efficacy and safety of brodalumab in nonobese vs. obese patients with psoriasis. Methods: This is a post hoc analysis of the prospective, phase III, multicentre, randomized, placebo‐ and active‐comparator‐controlled AMAGINE‐2 and AMAGINE‐3 trials, in which patients were randomized to treatment with brodalumab 210 mg every 2 weeks, ustekinumab or placebo for a 12‐week induction phase. At week 12, patients who received brodalumab 210 mg every 2 weeks continued brodalumab, those treated with ustekinumab continued ustekinumab, and those who received placebo switched to brodalumab 210 mg every 2 weeks. Patients were categorized by body mass index (BMI) category (< 30 or ≥ 30 kg m −2 ) and efficacy was evaluated using the physician‐rated Psoriasis Area and Severity Index and static Physician's Global Assessment instruments. Results: In total, 281 of 687 patients (40·9%) were obese. Skin clearance was comparable across BMI subgroups in brodalumab‐treated patients. Psoriasis Area and Severity Index 100% improvement rates in nonobese and obese patients at week 12 were 54·1% and 49·5%, respectively, and at week 52 they were 72·6% and 64·8%, respectively. Week 12 ustekinumab responses were lower than brodalumab responses and were 6–17% lower in obese than in nonobese patients. No appreciable differences in overall safety were observed between nonobese and obese patients. Conclusions: The efficacy and safety of brodalumab did not differ between patients with moderate‐to‐severe psoriasis who had a BMI < 30 kg m −2 or a BMI ≥ 30 kg m −2 . Abstract : What's already known about this topic? There is a well‐established association between psoriasis and obesity, with the risk of psoriasis directly related to body mass index. Obese patients with psoriasis often experience decreased efficacy and increased susceptibility to certain side‐effects of therapeutic agents, making effective treatment in this population challenging. What does this study add? This is the first evaluation to report the effects of brodalumab treatment on obese and nonobese patients with psoriasis. These data show that brodalumab is effective regardless of body weight or body mass index in patients with moderate‐to‐severe psoriasis. Linked Comment: Sbidian and Cleach. Br J Dermatol 2020; 182 :824–825.